10 MeV proton irradiation effects on GaInP/GaAs/Ge concentrator solar cells and their component subcells - Ochoa, M. (2017)
Fil: Yaccuzzi, Exequiel. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina